PROPOSAL FOR A DIRECTIVE OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL AMENDING DIRECTIVES 2009/102/EC AND (EU) 2017/1132 AS REGARDS FURTHER EXPANDING AND UPGRADING THE USE OF DIGITAL TOOLS AND PROCESSES IN COMPANY LAW – TRUST, TRANSPARENCY AND EASIER CROSS-BORDER EXPANSION FOR COMPANIES - Vasile NEMEȘ; Gabriela FIERBINȚEANU (Challenges of the Knowledge Society)
Digital tools are essential to ensure the continuity of business operations and of companies' interactions with business registers and authorities. The need to enhance trust and transparency in the business environment and to facilitate the operations of companies, in particular micro, small and medium-sized enterprises (SMEs) in the single market , was underlined since 2003 in Commission Recommendation 2003/361/EC1. As a consequence, in this digital era it is crucial to ensure access for companies, authorities and other stakeholders to reliable company information that can be used without burdensome formalities in a cross-border context. In response to developments in the digital environment, Directive (EU) 2017/11322 was amended by Directive (EU) 2019/1151 of the European Parliament and of the Council3 introducing rules for carrying out the following operations entirely online: incorporation of public limited liability companies, registration of cross-border branches and submission of documents to business registers. A new step is taken now with the Proposal for a Directive of the European Parliament and of the Council amending Directives 2009/102/EC and (EU) 2017/1132 as regards further expanding and upgrading the use of digital tools and processes in company law4. The new initiative complements Directive (EU) 2019/1151 focusing on additional segments where digitalisation could improve EU company law, by addressing the availability and reliability of company information in business registers and BRIS, and its use in cross-border situations.